Antioxidant activity and seed vigor in germination of bean under salt stress conditions - Padilha, Matheus Santin (2025)
Using seeds with higher physiological potential can help overcome saline stress, affecting many arable areas in tropical and subtropical regions. This study aimed to evaluate whether seed vigor contributes to overcoming saline stress, seeking to identify the association between the antioxidant system and seed lot vigor. Seeds of the BAF55 genotype with two levels of vigor were used. The seeds were germinated under no-stress conditions, with 75 and 150 mmol L-1 of sodium chloride in the solution during germination. After five days, morphological changes and changes in the enzyme’s catalase, ascorbate peroxidase, guaiacol peroxidase, proline, malondialdehyde, and hydrogen peroxide were evaluated. An increase in antioxidant activity was observed with the imposed stresses and no significant difference was observed between the vigor level, except in the condition of 75 mmol L-1 in the hypocotyl of the seedlings and, for proline in the condition of 150 mmol L-1 in which the low-vigor presented greater activity. The stress of 150 mmol L-1 showed greater severity in seeds of low-vigor, resulting in greater lipid peroxidation in the seedlings formed and resulting in seedlings with lower performance.